Investment Climate Development Strategy for North Maluku Economic Growth - Musdar Muhammad; Bahrun Talib; Daud Hasim (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyse and examine strategies for developing the business climate and investment in order to spur economic growth in North Maluku Province. The research method employed is a quantitative descriptive approach to formulate regional policy strategies. Secondary data consists of macroeconomic time-series data. The data was then analysed using the Analytical Hierarchy Process (AHP). The results indicate that the respondents’ preferences are valid and consistent, with an inconsistency ratio (CR) below the threshold (CR < 0.100). The main criteria prioritised for business climate development, in descending order, are Security (0.214), Investment (0.144), Public Services (0.107) and Licensing (0.103). At the sub-criterion level, security costs have the highest priority weighting (0.425); the electricity supply aspect shows a downward trend (0.199); barriers to business access are dominated by distribution and labour issues (0.193 each); and licensing requirements are still rated as poor (0.163).